Role-based responsibilities in securing research integrity: increasing support for multi-level implementers - Lõuk, Kristi (Frontiers in Research Metrics and Analytics, 2023)
This perspective article focuses on how researchers help to secure the research integrity-related responsibilities of various institutions in their various roles, as the same researcher can fulfill the tasks of different stakeholders, be in different roles, and wear multiple hats simultaneously while performing duties at different levels. Institutions whose research integrity-related responsibilities are carried out by researchers should support the multi-level implementers more in carrying out these roles and responsibilities and consider their input when setting up tasks. In addition to having necessary policies and procedures, these should be actionable and supported by responsible research culture and environment. Furthermore, policies and action plans should be created in consideration of and in co-creation with the actual implementers. Realizing that the multiple-level role of researchers also helps to secure research integrity at the institutional and system level of science should go hand in hand with creating responsible research culture and environment where that input is taken into account. This in turn will help researchers deal with various current pressures, e.g., having not enough time or being subject to unfair evaluations.